Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{2}{a}\cdot\frac{3}{7}\cdot\frac{1}{5}=\frac{6}{35}\)
\(\frac{2\cdot3\cdot1}{a\cdot7\cdot5}=\frac{6}{35}\)
\(\Rightarrow\frac{6}{a\cdot35}=\frac{6}{35}\)
\(\Rightarrow a\cdot35=35\)
\(a=35:35=1\)
P/s: Ủa rồi tìm x hay tìm a vậy bạn :D???
2/a x 3 / 7 x 1 / 5 = 6 / 35
2 / a x 3 / 7 = 6 / 35 : 1 / 5
2 / a x 3 / 7 = 6 / 7
2 / a = 6 / 7 : 3 / 7
2 / a = 2
= > a = 1
Học tốt
-NGL
a: =>x=3/7+3/5=15/35+21/35=36/35
b: =>x/35=4/5-5/7=28/35-25/35=3/35
=>x=3
c: =>x<3/4+8/4=11/4
=>\(x\in\left\{0;1;2;3\right\}\)
d: =>5/3<x<5/6+24/6=29/6
=>\(x\in\left\{2;3;4\right\}\)
e: =>x<10/12-9/12=1/12
=>x=0
f: =>2/3<x<12/6-5/6=7/6
=>x=1
\(1)\frac{12}{7}\times \frac{7}{4}+\frac{35}{11}:\frac{245}{121}\)
\(=3+\frac{35}{11}\times \frac{121}{245}\)
\(=3+\frac{11}{7}\)
\(= 3\frac{1}{7}(=\frac{22}{7})\)
\(\dfrac{3}{7}\times x=\dfrac{1}{3}\)
\(x=\dfrac{1}{3}:\dfrac{3}{7}\)
\(x=\dfrac{7}{9}\)
\(x:\dfrac{6}{8}=\dfrac{2}{5}\)
\(x=\dfrac{2}{5}\times\dfrac{6}{8}\)
\(x=\dfrac{6}{20}=\dfrac{3}{10}\)
\(x-\dfrac{2}{3}=\dfrac{5}{6}\)
\(x=\dfrac{5}{6}+\dfrac{2}{3}\)
\(x=\dfrac{9}{6}=\dfrac{3}{2}\)
\(x-\dfrac{2}{5}-\dfrac{4}{35}=\dfrac{1}{7}\)
\(x=\dfrac{1}{7}+\dfrac{4}{35}+\dfrac{2}{5}\)
\(x=\dfrac{23}{35}\)
.
a)4/9 : x/6 = 2/3
x/6 = 4/9 : 2/3
x/6 = 2/3 = 4/6
vậy x = 4
b)x/5 x 3/7 = 9/35
x/5 = 9/35 : 3/7
x/5 = 3/5
vậy x = 3
Tìm x:
\(a.\dfrac{35}{28}-x=\dfrac{5}{14}\\ x=\dfrac{35}{28}-\dfrac{5}{14}\\ x=\dfrac{25}{28}\\ b.\dfrac{6}{7}\times x=\dfrac{2}{3}\\ x=\dfrac{2}{3}:\dfrac{6}{7}\\ x=\dfrac{7}{9}\\ c.x\times7=\dfrac{3}{4}\\ x=\dfrac{3}{4}:7\\ x=\dfrac{3}{28}\\ d.2:x-\dfrac{1}{3}=\dfrac{2}{5}\\ 2:x=\dfrac{2}{5}+\dfrac{1}{3}\\ 2:x=\dfrac{11}{15}\\ x=2:\dfrac{11}{15}\\ x=\dfrac{30}{11}.\)
\(a,\dfrac{35}{28}-x=\dfrac{5}{14}\)
\(x=\dfrac{35}{28}-\dfrac{5}{14}\)
\(x=\dfrac{25}{28}\)
\(b,\dfrac{6}{7}\times x=\dfrac{2}{3}\)
\(x=\dfrac{2}{3}:\dfrac{6}{7}\)
\(x=\dfrac{7}{9}\)
\(c,x\times7=\dfrac{3}{4}\)
\(x=\dfrac{3}{4}:7\)
\(x=\dfrac{3}{28}\)
\(d,2:x-\dfrac{1}{3}=\dfrac{2}{5}\)
\(2:x=\dfrac{2}{5}+\dfrac{1}{3}\)
\(2:x=\dfrac{11}{15}\)
\(x=2:\dfrac{11}{15}\)
\(x=\dfrac{30}{11}\)
#YVA
a: \(\dfrac{1}{8}\cdot\dfrac{4}{5}:\dfrac{3}{5}=\dfrac{1}{10}\cdot\dfrac{5}{3}=\dfrac{1}{2\cdot3}=\dfrac{1}{6}\)
b: \(=\dfrac{8-3}{12}\cdot\dfrac{6}{5}=\dfrac{6}{12}=\dfrac{1}{2}\)
c: \(=\dfrac{24}{35}:\dfrac{32}{35}=\dfrac{3}{4}\)
d: =63/21+15/21-7/21=71/21
a \(\dfrac{1}{8}\times\dfrac{4}{5}\times\dfrac{10}{6}=\dfrac{1}{6}\)
b \(\left(\dfrac{8}{12}-\dfrac{3}{12}\right)\times\dfrac{6}{5}=\dfrac{5}{12}\times\dfrac{6}{5}=\dfrac{1}{2}\)
c \(\dfrac{24}{35}:\dfrac{32}{35}=\dfrac{24}{35}\times\dfrac{35}{32}=\dfrac{3}{4}\)
d \(\dfrac{63}{21}+\dfrac{15}{21}-\dfrac{7}{21}=\dfrac{71}{21}\)
\(\frac{x}{50}\)= \(\frac{1}{10}\)
\(\frac{x}{50}\)= \(\frac{5}{50}\)
=> x= 5
Vậy x=5
\(\frac{35}{x}\)= \(\frac{5}{6}\)
\(\frac{35}{x}\)= \(\frac{35}{42}\)
=> x=42
Vậy x=42
`x + 1/5 - 3/7 = 6/35`
`x + 7/35 - 15/35 = 6/35`
`x - 8/35 = 6/35`
`x=6/35 + 8/35`
`x= 14/35`
`x=2/5`
Vậy `x= 2/5`
x+1/5-3/7=6/35
x+1/5=6/35+3/7
x+1/5=3/5
x=3/5-1/5
x=2/5